PEMBUATAN LKS ICT IPA TERPADU MENGINTEGRASIKAN KARAKTER MATERI SISTEM PENCERNAAN, BAHAN KIMIA, DAN TEKANAN ZAT CAIR UNTUK SISWA SMP KELAS VIII - Dina Syaflita; Asrizal Asrizal; Harman Amir (PILLAR OF PHYSICS EDUCATION, 2016)
ICT student worksheet of integrated science by integrating character values is a learning solution for 2013 curriculum. The purpose of this research is to determine the validity, description, practicality, and effectiveness of ICT student worksheet of integrated science by integrating character values. The type of research is Research and Development (R&D). The design of this research is before and after of treatment. The object of research is ICT student worksheet of integrated science by integrating character values. Instruments to collecting data are validity instrument, practicality instrument, and effectiveness instrument that consist of knowledge test sheet, observation sheet, and performance sheet. There are three data analysis, those are description statistic, graph method, and correlated t-test. This research gives two main results. First, worksheet validity is in very valid criteria. Product description is good criteria. Second, worksheet practicality is in very practice criteria. ICT student worksheet of integrated science by integrating character values to digestive system, chemical material, and pressure of liquid substance for 8th grade junior high school student are effective used in science learning activity